The significance of the virtue of friendliness for moral education in the age of artificial intelligence (AI) - Yasin, Maizura; Mohamed Mokhtar, Marzni; Le, Song (Universiti Putra Malaysia Press, 2024)
Since 2022, Artificial Intelligence (AI), represented by ChatGPT, has changed human lifestyles and productivity. The development of AI technology is also more closely integrated with the progress of human society. In the context of the rapid development of this revolutionary technology, people's traditional moral principles are facing unprecedented challenges. In the background of the artificial intelligence era, this study focuses on exploring the concept of the virtue of friendliness and emphasizes its importance in moral education and ethical practice. Firstly, this study is based on Aristotle's virtue ethics and the Chinese Confucian traditional ethics to redefine the concept of the virtue of friendliness and clarify its essential noble qualities for human beings. After this, this study also explores the impact of the development of AI technology on the practice of the virtue of friendliness to highlight its significance for people's moral behaviour. Researchers advocate enhancing moral education on the virtue of friendliness to respond to increasingly complex ethical issues through the development of AI. This study not only provides a new way to inherit and develop traditional virtue ethics in the context of AI technology but also illustrates the significance of the virtue of friendliness in moral education in shaping people’s moral behaviours.